DNA cleavage, structural elucidation and anti-microbial studies of three novel mixed ligand Schiff base complexes of copper(II) - N. RAMAN (Journal of the Serbian Chemical Society, 2007)
Three new copper complexes of mixed ligands derived from Schiff bases (condensation of p-aminoacetanilide and substituted benzaldehydes) with 1,10-phenanthroline have been synthesized and characterized by elemental analysis, IR, UV–Vis, magnetic moments, conductivity and electrochemical measurements. The spectral techniques suggest that all the copper complexes exhibit octahedral geometry. The low electrical conductance of the complexes supports their neutral nature. The monomeric nature of the complexes was assessed from their magnetic susceptibility values. The in vitro biological screening effects of the investigated compounds were tested against the bacteria Escherichia coli, Staphylococcus aureus, and Salmonella typhi and the fungi Rhizopus stolonifer and Candida albicans by the serial dilution method. A comparative study of the MIC values of the Schiff bases and their copper complexes indicates that the metal complexes exhibited higher antibacterial activity than the free ligands. The DNA cleavage ability of the complexes was monitored by the gel electrophoresis technique. It was found that electron withdrawing group substituted copper complex had higher DNA cleavage activity than the other copper complexes.